The Analysis of Islamic Moral and Faith (Aqidah Akhlak) Learning Methods in Improving Understanding of Character Education of Students at SMP YASPEND AN-NAAS BINJAI - Nauli, Putri Anggi (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2024)
This paper is entitled Analysis of Islamic Moral and Faith Learning Methods in Improving Students' Understanding at SMP YASPEND AN-NAAS BINJAI. This paper used a qualitative approach and literature study methods. Based on the results of the discussion, in the process of implementing learning, a teacher has a very important role in helping students to try to develop their potential and moral development, and it is done continuously. In internalizing the learning method, various methods are carried out so that students become individuals who have good character, and become a generation that has faith and piety. To achieve this goal, the development of faith and piety can be done through several methods, such as the Imitation method, the Amtsal method, and the Observation method as an increase in students' understanding of the character education that will be formed. This paper was made with the aim that there was a sense of mutual knowledge and understanding of these basic concepts. The foundation used in explaining the method of learning Islamic moral and faith in increasing understanding of character education is guided by Islamic teachings so that the references used are the Al-Quran and Sunnah and the opinions of scholars who concentrate on Islamic education. Thus, Islamic Religious Education educators must evaluate students' development, including aspects of aqliyah, qolbiyah, and amāliyah.